Analisis Pelaksanaan Rekredensial dan Adaptasi Budaya Kerja Baru terhadap Kinerja Perawat RS Bina Husada - Khoiriyah, Khoiriyah; Hadi, Muhammad; Naryati, Naryati; Suminarti, Tini (Universitas Malahayati, 2025)
ABSTRACT Re-credentialing is a re-evaluation process for nursing staff who already have clinical authority to determine the appropriateness of granting clinical authority. Implementing the new work culture acquired by the hospital, which includes caring, respect, empathy, innovativeness, and teamwork, is expected to influence the performance of nurses in providing services at the hospital. This research was conducted to analyze the relationship between recruitment and adaptation to a new work culture on the performance of nurses at Bina Husada Cibinong Hospital. This research design uses descriptive analytics with a cross-sectional approach. The total sample for this research was 79 respondents. The multiple logistic regression test found that credentials and work culture were most related to nurse performance with a new work culture p-value of 0.018 and OR 461.878, and credentials p-value of 0.018 and OR 2.090. Based on the results of multiple logistic regression, it was found that the work culture variable was the factor most related to the performance of nurses at Bina Husada Cibinong Hospital. The majority of nurses' performance is good, with the most significant variables related to performance being re-credentials and work culture adaptation. Keywords: Nurse Performance, Re-credentials, Work Culture Adaptation. ABSTRAK Rekredensial adalah proses re-evaluasi terhadap tenaga keperawatan yang telah memiliki kewenangan klnis untuk menentukan kelayakan pemberian kewenangan klnis. Pelaksanaan budaya kerja baru yang mengakuisisi RS, yang meliputi caring, respect, empathy, innovative dan Teamwork diharapkan dapat mempengaruhi kinerja perawat dalam memberikan pelayanan di Rumah sakit. Penelitian ini dilakukan untuk menganalisis hubungan rekredensial dan adaptasi budaya kerja baru terhadap kinerja perawat di RS Bina Husada Cibinong. Desain penelitian ini menggunakan deskriptif analitik dengan pendekatan cross sectional. Jumlah sampel penelitian ini adalah 79 responden. Dari uji regresi logistik ganda didapatkan rekredensial dan budaya kerja yang paling berhubungan dengan kinerja perawat dengan budaya kerja baru p-value 0,018 dan OR 461,878, serta rekredensial p-value 0,018 dan OR 2,090. Berdasarkan hasil regresi logistik berganda didapatkan hasil variabel budaya kerja merupakan faktor yang paling berhubungan dengan kinerja perawat di RS Bina Husada Cibinong. Mayoritas kinerja perawat baik, dengan variabel yang paling signifikan dengan kinerja adalah rekredensial dan adaptasi budaya kerja. Kata Kunci: Adaptasi Budaya Kerja, Kinerja Perawat, Rekredensial.